Navigating the uncertainties of next‐generation sequencing in the genetics clinic. Issue 3 (3rd October 2022) - Kuiper, Janneke M. L.; Borry, Pascal; Vears, Danya F.; Van Esch, Hilde; Van Hoyweghen, Ine
Abstract: This study explores the different manifestations and navigations of uncertainty in the practice of diagnostic next‐generation sequencing (NGS) testing. Drawing upon multi‐sited fieldwork conducted at a large Centre for Human Genetics in Belgium, we analyse how uncertainty takes shape and is managed in the different steps of the diagnostic process: starting from the testing offer, to the analysis in the lab, the multidisciplinary team meetings (MDTs) and ending with the consultation with the patient. Building on interviews with genetic healthcare professionals and their patients and observations in consultations and MDTs, our empirical work underlines the duality of uncertainty as both burdensome and productive. Building on the existing literature on uncertainty in medicine and NGS, our analysis shows the ontological politics at play in the everyday uncertainty work in this CHG. We show how the, at times, contrasting ways of dealing with uncertainty lead to friction but also result in constructive negotiation and collaboration between actors, making use of multiple types of evidence and expertise. By not only minimising but also sustaining or inviting uncertainty, genetic healthcare professionals are able to advance the practices around NGS in a way that matches their multidisciplinary understandings, considerations and more normative stances.